2020
DOI: 10.21873/anticanres.14138
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Exosomal Micro RNA Biomarkers Related to Epithelial-to-Mesenchymal Transition in Pancreatic Cancer

Abstract: Background/Aim: Epithelial-to-mesenchymal transition (EMT) plays important roles in cancer progression. This study aimed to identify the exosomal miRNA (exo-miRNA) profiles related to the EMT status in pancreatic cancer (PC). Materials and Methods: Comprehensive exo-miRNA-expression profiles in the culture media of PC cell lines were analyzed through microarray technology. The identified miRNAs were analyzed to investigate their clinical implication using The Cancer Genome Atlas (TCGA) dataset and clinical sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Interestingly, bone marrow MSCs-derived exosomes are capable of restraining NSCLC cell malignant phenotype in vitro and inhibiting the tumor growth in vivo by delivering miR-144 to NSCLC cells [38]. Exosomal miR-204-3p regulating EMT in pancreatic cancer has also been confirmed [39]. In our study, MSCs-derived exosome-shuttled miR-204 was found to suppress NSCLC progression via mediation of the KLF7/AKT/HIF-axis.…”
Section: Discussionsupporting
confidence: 62%
“…Interestingly, bone marrow MSCs-derived exosomes are capable of restraining NSCLC cell malignant phenotype in vitro and inhibiting the tumor growth in vivo by delivering miR-144 to NSCLC cells [38]. Exosomal miR-204-3p regulating EMT in pancreatic cancer has also been confirmed [39]. In our study, MSCs-derived exosome-shuttled miR-204 was found to suppress NSCLC progression via mediation of the KLF7/AKT/HIF-axis.…”
Section: Discussionsupporting
confidence: 62%
“…They can selectively carry and encapsulate miRNA “goods,” and in a separation cycle, exosomal miRNAs can reduce or eliminate interferences from nonexosomal miRNAs to the cycle, which enhances the credibility and reliability of exosomal miRNA profiles in the diagnosis. Over the past few years, several results on miRNA sequencing of serum or plasma exosomes were reported in colorectal [ 27 ], lung [ 28 30 ], liver [ 31 , 32 ], pancreatic [ 33 ], and thyroid cancers [ 34 ], indicating a new approach for tumor diagnosis. The expression of miR-6803-5p in the serum exosomes from colorectal cancer patients is higher than that in the serum exosomes from healthy controls, and its expression in the exosomes is correlated with poor prognosis of colorectal cancer patients (ROCAUC = 0.7399), suggesting that exosomal miR-6803-5p can serve as a potential diagnostic and prognostic biomarker for colorectal cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study using cationic liposome-based nano-biochips, the researchers detected increased plasma exosomal miR-21 and miR-10b in pancreatic cancer patients, suggesting that plasma exosomal miR-21 and miR-10b serve as noninvasive diagnostic biomarkers for early pancreatic cancer [ 33 ]. Relying on gene chip technology, another study on pancreatic cancer discovered that miR-196b-3p and miR-204-3p in the serum exosomes of pancreatic cancer patients act as diagnostic biomarkers for pancreatic cancer [ 34 ]. A study on thyroid cancer using small RNA sequencing revealed that miR-485-3p and miR-4433a-5p in plasma exosomes are diagnostic biomarkers for papillary thyroid cancer and that miR-485-3p can be used to distinguish high-risk from low-risk papillary thyroid cancer [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA-339-5p levels were significantly lower than in classic tumor cells, hypothetically through an effect on its target, zinc-finger protein ZNF689 known to promote tumor progression [ 27 ]. Such impact of tumor cell-derived exosomal-miRNA on migration and invasion is further strengthened by a report from Sonohara et al highlighting the association with epithelial-to-mesenchymal transition (EMT) [ 28 ]. In contrast to the above studies, upregulated and functional miR-222 transfer from highly invasive to non-invasive cells via exosomes was experimentally confirmed, promoting cell invasion and proliferation in recipient cells through subsequent phosphorylation and activation of Akt, relocalizing p27 to the cytoplasm, thus suppressing its capacity as a tumor suppressor in the nucleus [ 29 ].…”
Section: Tumor Cells Evs-mediated Crosstalkmentioning
confidence: 94%